2021
DOI: 10.21203/rs.3.rs-138423/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparison of Genomic Characterization in Upper Tract Urothelial Carcinoma and Urothelial Carcinoma of the Bladder

Abstract: Background: Different genomic characterization in urothelial carcinoma (UC) by site of origin, may imply contrasting therapeutic opportunities and pathogenetic mechanisms. The aim of this study was to investigate whether the differences between upper tract urothelial carcinoma (UTUC) and urothelial carcinoma of the bladder (UCB) result from intrinsic biological diversity.Methods: We prospectively sequenced 118 tumors and matched blood DNA from Chinese UC patients using next-generation sequencing (NGS) techniqu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…However, at present, there is no consensus on the frequency and maintenance time of bladder perfusion after UTUC [14] . Although the morphology of UTUC is the same as that of bladder urothelial carcinoma, studies have shown some differences in biological characteristics and related gene expression [15,16] . EUA guidelines recommend that UTUC should be treated with single intravesical infusion chemotherapy immediately after the radical resection of pyelopelvic carcinoma, which can reduce the risk of recurrence of bladder tumor in the rst year after resection.…”
Section: Discussionmentioning
confidence: 99%
“…However, at present, there is no consensus on the frequency and maintenance time of bladder perfusion after UTUC [14] . Although the morphology of UTUC is the same as that of bladder urothelial carcinoma, studies have shown some differences in biological characteristics and related gene expression [15,16] . EUA guidelines recommend that UTUC should be treated with single intravesical infusion chemotherapy immediately after the radical resection of pyelopelvic carcinoma, which can reduce the risk of recurrence of bladder tumor in the rst year after resection.…”
Section: Discussionmentioning
confidence: 99%